Using Nikiforov-Uvarov Method to Find the Single-Particle Nuclear States for Harmonic-Oscillator Potential - Rahim, Aziz H.; Abdullah, Nzar R. (Science Journal of University of Zakho, 2018)
In this study the energy spectrum and Eigenvectors with a special type of central potential will be obtained by using Nikiforov-Uvarov method. The method covers a new algebraic technique to  make an exact diagonalization to find the eigenvalues and eigenvectors of the Hamiltonian of the harmonic oscillator (HO).
Keywords: Central potential; Nikiforov-Uvarov method; harmonic oscillator